Impact of Culture on ‘Partner Selection Criteria’ in East Asian International Joint Ventures - ZUTSHI, Ravinder K. (Institutional Knowledge at Singapore Management University, 2009)
Selecting the right partner is important for the success of alliances and joint ventures. For international joint ventures (IJVs) from diverse cultures the partner selection process can become complicated. Prior studies have investigated the alliances and joint ventures to develop a set of objective criteria for evaluating potential partners. This paper reports the study of IJVs formed by Singapore firms in Peoples Republic of China and India. The intent was to develop a methodology for identifying partner selection criteria in a cross-cultural setting. The findings reveal that the partner selection process follows a different logic in Confucian societies. Trust has been established to be essential for developing enduring co-operative relationships. The paper explores the concept of trust in relation to commitment and control in the context of the Confucian culture. We discover that trust is critical to partner selection. Cultural differences do not significantly alter the partner selection criteria for Singapore firms. Results support the view that while Chinese may depend on networks for social solidarity, social trust does extends beyond the family and is necessary for harmonious and successful joint ventures.